Banjar Traditional House Bubungan Tinggi Teluk Selong Ulu Banjar Regency - Muhammad Ihsan; Jumriani Jumriani; Muhammad Rezky Noor Handy; Sovia Husni Rahmia; Syarifuddin Syarifuddin (The Innovation of Social Studies Journal, 2024)
Banjar Traditional Houses, such as Rumah Bubungan Tinggi, are an important representation of Banjar's cultural identity and are protected as cultural heritage. Facing the challenges of globalization and changing times, it is important to maintain and preserve local culture through education, participation in cultural activities, and tourism promotion that highlights local uniqueness. This study aims to describe the condition of the Bubungan Tinggi Traditional House in Selong Ulu Bay as a tourist attraction and to explore its preservation efforts. Using descriptive qualitative methods through observation, interviews, and documentation, this study found that although the Bubungan Tinggi Traditional House still functions as a tourist destination, its condition is fragile due to the age of almost 200 years and there is a lack of promotion and information about this traditional house. The visit activities are carried out free of charge, but the use of social media and collaboration with young people are needed to increase visitor interest and preserve culture. The conclusion of this study is that although the Bubungan Tinggi Traditional House is still active as a tourist attraction, regular cultural preservation and cultural development are needed to increase economic benefits for the local community and ensure the sustainability of the cultural heritage.